Preaching from the Old Testament - Brueggemann, Walter 1933-2025 (Minneapolis Fortress Press, 2019)
Preaching from the Torah : Genesis -- Preaching from the Torah : the tale of Moses -- Preaching from the prophets -- Preaching from the Psalms -- Preaching from the wisdom traditions.
In this new volume, prolific scholar Walter Brueggemann seeks to show Christian preachers how to consider the faith witnessed in several Old Testament traditions and to help them discover rich and suggestive connections to our contemporary faith challenges. The author also assumes that a wholesale sustained engagement with the Old Testament is worth the effort for the preacher. He recognizes what he calls the "sorry state" of Old Testament texts in the Revised Common Lectionary, which he claims often constitute a major disservice for the church and its preachers. The lectionary gerrymanders the Old Testament to make it serve other claims, most of the time not allowing it to have its own evangelical say. Brueggemann hopes that his exposition in this volume will evoke and energize fresh homiletical attention to the Old Testament, precisely because he believes the urgent work of the gospel in our society requires attentive listening to these ancient voices of bold insistent faith
Includes bibliographical references and index
Keywords: Bible -- Homiletical use; Bible -- Criticism, interpretation, etc; Bible; Criticism, interpretation, etc